2015
DOI: 10.3109/17549507.2014.979872
|View full text |Cite
|
Sign up to set email alerts
|

Does language learning disability in school-age children affect semantic word learning when reading?

Abstract: Results indicated that children with LLD show limitations gaining semantic knowledge of novel words during reading, which could negatively impact their overall rate of vocabulary acquisition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 52 publications
1
10
2
Order By: Relevance
“…The rate of word knowledge growth across three exposures did not differ according to participants' language ability. This finding conflicts with that of Steele (2015), who found that children with LLD, but not their typically developing ageor vocabulary-matched peers, benefited from additional exposure. However, our finding is consistent with that reported by Steele and Watkins (2010) indicating that groups of school-age children with LLD and typical language responded similarly to varying levels of exposure to novel words during silent reading.…”
Section: Effects Of Language Skillcontrasting
confidence: 80%
“…The rate of word knowledge growth across three exposures did not differ according to participants' language ability. This finding conflicts with that of Steele (2015), who found that children with LLD, but not their typically developing ageor vocabulary-matched peers, benefited from additional exposure. However, our finding is consistent with that reported by Steele and Watkins (2010) indicating that groups of school-age children with LLD and typical language responded similarly to varying levels of exposure to novel words during silent reading.…”
Section: Effects Of Language Skillcontrasting
confidence: 80%
“…There were only four studies that primarily investigated word learning in the written modality. For instance, Steele and colleagues presented novel word stimuli via an independent reading task and assessed how well children learned new word meanings (Steele , Steele and Watkins , Steele et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…). Similarly, Steele and colleagues explored frequency effects on word learning in the written modality, presenting novel words in ‘low rate’ (two presentations in the text) and ‘high rate’ (five presentations) conditions (Steele , Steele and Watkins , Steele et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations